Mapping Knowledge Structure and Themes Trends of Post-operative Rehabilitation of Hip Fractures in the Elderly: A Bibliometrics and Visualization Study - Hu, Liuchao; Wei, Qiushi; Luo, Ziheng; Wang, Bin; Wu, Zhifang; He, Mincong; He, Xiaoming; Luo, Yiwen (Frontiers in Surgery, 2022)
Background Hip fractures are a common type of fracture in the elderly and are characterized by many complications and high mortality. Many topics concerning postoperative rehabilitation of hip fracture in elderly people still remain controversial, and the global research trend in this field has not yet been well studied. The aim of the present study was to illustrate the overall knowledge structure, development trends, and research hot spots of postoperative rehabilitation of hip fracture in elderly people. Methods Articles and reviews regarding postoperative rehabilitation of hip fracture in elderly people from 2001 to 2021 were identified from the Web of Science database. An online bibliometric platform, CiteSpace, and VOSviewer software were used to generate visualization knowledge maps, including annual trends of publications, contributions of countries, institutions, authors, funding agencies, and journals, and clustering of keywords. Results A total of 1,724 publications were identified from Web of Science Core Collection (WoSCC). In the past 20 years, the number of published studies on the rehabilitation of hip fracture in the elderly has exhibited an overall upward trend. The USA was the leading contributor in this field, with the largest number of publications (354, 20.65%) and the most citations (13,786 times). The international cooperation map among relevant countries/regions indicated that the USA collaborated most closely with Canada and China. The University of Maryland and Professor Marcantonio were the most prolific institution and influential author, respectively. Injury: International Journal of the Care of the Injured was the most productive journal concerning the research of postoperative rehabilitation of hip fracture in elderly people. The keyword co-occurrence analysis identified six clusters: quality of life study, rehabilitation and outcomes study, cognitive impairment study, operative approaches study, mortality study, and osteoporosis study. Conclusions There will be an increasing number of publications on the research of postoperative rehabilitation of hip fracture in elderly people, and the United States will stay ahead in this field. Our findings could offer practical sources for scholars to understand the current status and trend of studies on rehabilitation of hip fracture in the elderly and provide references and suggestions for the development of related research in future.